HKB99, an allosteric inhibitor of phosphoglycerate mutase 1, suppresses invasive pseudopodia formation and upregulates plasminogen activator inhibitor-2 in erlotinib-resistant non-small cell lung cancer cells - Liang Qian; Gu Wei-ming; Huang Ke; Luo Ming-yu; Zou Jing-hua; Zhuang Guang-lei; Lei Hui-min; Chen Hong-zhuan; Zhu Liang; Zhou Lu; Shen Ying (Acta Pharmacologica Sinica, 2021)
Acquired resistance to epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs), such as erlotinib, remains a major challenge in the targeted therapy of non-small cell lung cancer (NSCLC). HKB99 is a novel allosteric inhibitor of phosphoglycerate mutase 1 (PGAM1) that preferentially suppresses cell proliferation and induces more apoptosis in acquired erlotinib-resistant HCC827ER cells compared with its parental HCC827 cells. In this study we identified the molecular biomarkers for HKB99 response in erlotinib-resistant HCC827ER cells. We showed that HCC827ER cells displayed enhanced invasive pseudopodia structures as well as downregulated plasminogen activator inhibitor-2 (PAI-2). Meanwhile, PAI-2 knockdown by siPAI-2 candidates decreased the sensitivity of HCC827 parental cells to erlotinib. Moreover, HKB99 (5 μM) preferentially inhibited the invasive pseudopodia formation and increased the level of PAI-2 in HCC827ER cells. Collectively, this study provides new insight into the role of PAI-2 in regulating the sensitivity of erlotinib resistant NSCLC cells to PGAM1 inhibitor. Furthermore, PAI-2 level might be considered as a potential biomarker for predicting the efficacy of the PGAM1 allosteric inhibitor on the erlotinib resistant NSCLC cells.